Level of Student’s Satisfaction on TVET Course Structure in Online Learning during Pandemic COVID-19 - Abdullah, Hannanah; Rozali, Mohd Zulfadli (Research and Innovation in Technical and Vocational Education and Training, 2022)
The COVID-19 pandemic has affected educational institutions worldwide when traditional face-to-face education is no longer appropriate to conduct during the COVID-19 pandemic to meet the demands of physical distance as an initiative to curb the spread of the COVID-19 pandemic. The shift in learning from traditional face-to-face learning to online learning that occurs drastically to ensure the continuity of education can affect the level of satisfaction Technical & Vocational Education and Training (TVET) students. This study aimed to identify students’ satisfaction with course TVET structure in online learning due to the spread of the COVID-19 pandemic. The design of this study was a survey study using a quantitative correlation approach. 179 TVET students were involved in the online survey questionnaire via Google Form. These data were analysed using descriptive analysis using the mean score, and standard deviation. The study findings show a high level of student satisfaction with the course structure. The study results indicate the need for developing an online learning framework, especially in the endemic situation, so that we can prevent students from facing low motivation to study.